2020
DOI: 10.5604/01.3001.0013.7955
|View full text |Cite
|
Sign up to set email alerts
|

Why do Polish medical students resign from pursuing surgical careers? A survey study

Abstract: Background: In recent years the interest of Polish medical students in choosing a career in surgical subspecialties has been declining. In the face of growing demand for surgical procedures it seems essential to find the reasons responsible for that situation. The aim of the study was to evaluate the level of interest in pursuing surgical careers among Polish medical students and to identify factors that may influence their decision. Material and methods: The anonymous questionnaire was distributed electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…One of the strengths of our study is providing new and previously uncollected data. So far, no nationwide study in this area has been conducted; rather, studies on the choice of a specific medical specialization [ 11 ] or single-center study [ 12 ] are available. The added value of this study is new evidence: our findings confirmed that work-life balance and flexible working conditions are crucial factors determining medical specialty selection by young doctors.…”
Section: Discussionmentioning
confidence: 99%
“…One of the strengths of our study is providing new and previously uncollected data. So far, no nationwide study in this area has been conducted; rather, studies on the choice of a specific medical specialization [ 11 ] or single-center study [ 12 ] are available. The added value of this study is new evidence: our findings confirmed that work-life balance and flexible working conditions are crucial factors determining medical specialty selection by young doctors.…”
Section: Discussionmentioning
confidence: 99%
“…Aljehani et al [ 29 ] show that orthopedic residents have been affected by a considerable amount of stress, and hospitals need to make recommendations in order to guide them. Career orientation is affected by gender discrimination [ 30 ], limited participation in surgery [ 31 ], and personality differences in relation to the surgeons who must train them [ 32 ]. Along with these, perspective change in professional orientation may be due to the mental state of residents during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The authors explained the phenomenon by the fact that expectations are inconsistent with reality, and also noted that a student who enters the operating room for the first time after the second year has a greater risk of abandoning plans for surgical specialization. 1 Another study included 261 Harvard students, 22% of women and 27% of men were interested in surgery. 64.7% of women and 60.7% of men stated that they were verbally discouraged from taking up surgical specialization.…”
Section: Students Are Not Interested In Surgerymentioning
confidence: 99%
“…According to research, medical students did not feel confident in performing manual procedures. 1,54 Due to the COVID-19 pandemic and related lockdowns, students' learning of practical skills has further deteriorated. 55 In the Skorus publication, students negatively assessed learning surgery during classes and indicated their lack of self-confidence as a factor discouraging them from choosing surgery.…”
Section: Surgical Skill Training During Studiesmentioning
confidence: 99%
See 1 more Smart Citation